STUDI KOMPARATIF KINERJA PORTOFOLIO OPTIMAL PADA KELOMPOK SAHAM KAPITALISASI BESAR DAN KAPITALISASI KECIL DI BEI - savitri, ni made anita dwi; purbawangsa, ida bagus anom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.11.TAHUN 2019, 2019)
The purpose of this study is to determine the performance comparison of large capitalization shares and small capitalization stocks. The results of the previous single index model approach found that of the 35 shares that were incorporated and used as research samples in the large capitalization index of 18 shares and in the small capitalization index of 18 stocks from January 2017 to January 2018 there were 25 stocks that could form an optimal portfolio , these shares include 13 shares of large capitalization and 12 shares of small capitalization. The results of this study indicate that the large capitalization stock portfolio has a sharpe index of -21.70, while the portfolio of small capitalization shares has a sharpe index of -39.33. If there is nothing better compared to the IHSG benchmark. However, the performance of shares can be measured by comparing each other into stocks that are able to show better performance, namely large capitalization shares with a value of -21.70 because the performance measure is better than small capitalization shares with a value of -39.33.